VALUE ADDITION AND STORABILITY OF DIFFERENT J UE ADDITION AND STORABILITY OF DIFFERENT JAMUNMANGO BLENDS MANGO BLENDS - DEEP SHIKHA SHARMA AND JAGMOHAN SINGH, (The Bioscan, 2018)
An experiment was carried out to study the value addition of blended jamun-mango juice. Jamun and mango juices were blended in the ratio of T1 (100:00 jamun: mango), T2 (90:10:: jamun: mango), T3(80:20:: jamun: mango), T4 (70:30:: jamun: mango) and T5 (60:40:: jamun: mango) for the preparation of ready- to- serve beverages. During six months of storage, the pH, reducing and total sugar contents of jamun mango blended ready to serve beverage of different treatments increased while phosphorus and tannin content decreased, respectively. The analysis of ready to serve beverage reveled that T5 (60:40:: jamun: mango) recorded the highest phosphorus (4.41 mg/100g), reducing (7.06 percent) and total sugar contents of 11.43 percent. Treatment T3(80:20 ::jamun: mango) was adjudged the best for retaining the maximum tannin and phosphorus contents even after 6 months of storage. All the samples were found to be free from microbial count upto four months of storage. However after six months of storage only treatments T4(70:30:: jamun: mango) and T5(60:40:: jamun: mango) showed a negligible count of 1×106 (CFU/ml) which might have occurred during handling etc and was in safe zone.